1957
DOI: 10.1002/jsfa.2740081212
|View full text |Cite
|
Sign up to set email alerts
|

Changes in carbohydrate, nitrogen and organic acid distribution in grass preserved with sodium metabisulphite

Abstract: Sodium metabisulphite appears to be an effective preservative for grass, giving a fresh‐coloured, pleasant‐smelling material of higher pH than normal silage. The metabisulphite acts as a bacteriostatic agent, permitting little bacterial fermentation; very considerable proteolysis and hydrolysis of carbohydrate takes place without the losses of resultant units normally associated with bacterial fermentation. The hydrolysed protein appears almost quantitatively as amino‐acid and peptide with little ammonia forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1957
1957
1995
1995

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…This is not a valid argument since ammonia N is a measure of amino acid deamination (MacPherson et al, 1957). Thus, our findings give support to the theory that conventional indicators of silage quality may not always be indicative of its potential nutritive value (Mayne and Steen, 1990), particularly if protein status of silage is important in terms of animal production response, as indicated by the findings of Charmley and Veira (1990).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is not a valid argument since ammonia N is a measure of amino acid deamination (MacPherson et al, 1957). Thus, our findings give support to the theory that conventional indicators of silage quality may not always be indicative of its potential nutritive value (Mayne and Steen, 1990), particularly if protein status of silage is important in terms of animal production response, as indicated by the findings of Charmley and Veira (1990).…”
Section: Discussionsupporting
confidence: 78%
“…Despite the long historical association of ammonia N content with the extent of proteolysis in silage (McDonald et al, 1991), statistical analysis indicated that there was a poor coaelation between ammonia N concentration and FILP content It is generally considered that low concentrations of ammonia N (<100 g kg"' total N) indicate low levels of proteolysis. This is not a valid argument since ammonia N is a measure of amino acid deamination (MacPherson et al, 1957). Thus, our findings give support to the theory that conventional indicators of silage quality may not always be indicative of its potential nutritive value (Mayne and Steen, 1990), particularly if protein status of silage is important in terms of animal production response, as indicated by the findings of Charmley and Veira (1990).…”
Section: Discussionsupporting
confidence: 45%
“…Volatile-N increased soon after baling or stacking (W, 1960; A and SA, 1961), and was correlated with actinomycetes growing a t 60' and with bacteria growing a t 60". In silage, extensive ammonia production usually occurs only in the presence of micro-organisms (Kemble, 1956;Macpherson et al 1957), but Brady (1960but Brady ( , 1961 reported that plant enzymes produced some ammonia.…”
Section: P H Gregory and Othersmentioning
confidence: 99%
“…Because ofthe difficulty involved in handling acids, there has been considerable interest in acid salts or acids in solid form, which are easier to handle. One of these additives is sodium metabisulphite and there is a good deal of information on its use (2,3,6,22,29). It can be very efficient as an additive, but it is subject to oxidation when oxygen is present in the mass and, being soluble, it is liable to seepage losses.…”
Section: Additives Which Inhibit Fermentationmentioning
confidence: 99%